Critical appraisal and comparison of recommendations of clinical practice guidelines for treatment of schizophrenia in children and adolescents: a methodological survey protocol - Cristiane de Cássia Bergamaschi; Silvio Barberato-Filho; Izabela Fulone; Maíra Ramos Alves; Flávia Blaseck Sorrilha; Rejane Coan Ferretti Mayer; Daniela Oliveira de Melo; Luciane Lopes (BMJ Open)
Introduction The number of clinical practice guidelines (CPGs) have increased substantially mainly in the paediatric area of mental health. However, little is known about the quality or how recommendations for the treatment of disorders such as schizophrenia in children and adolescents have changed over time. The aim of this study will be to assess the quality of the development of CPGs for the treatment and management of schizophrenia in children and adolescents over time using the Appraisal of Guidelines for Research and Evaluation II (AGREE II) tool and to compare the recommendations and interventions described in these documents.Methods and analysis CPGs will be identified using a prospective protocol through a systematic search of multiple databases (Medline, Embase, Health Systems Evidence, Epistemonikos, Lilacs, etc) and guideline websites from 2004 to December 2020. The quality of the guidelines will be assessed by three reviewers, independently using the AGREE II. CPGs will be considered of high-quality if they scored ≥60% in four or more domains of the AGREE II instrument. Non-parametric tests will be used to test for the change of quality over time. We will summarise the different evidence grading systems and compare the recommendations.Ethics and dissemination Ethical approval is not required since it is a literature-based study. Future results of the research can be submitted for publication in scientific journals of high impact, peer reviewed and also published in national and international conferences. The results derived from this study will contribute to the improvement of health institutions and policies, informing about existing recommendation guidelines and about deficiencies and qualities found in those. This study may also identify key areas for future research. This study may guide the search and choice for high quality CPGs by health policy makers and health professionals and subsidise future adaptations.Protocol registration number CRD42020164899.